„Ślub” w manierze performatywnej - Krajewska, Anna (Przestrzenie Teorii, 2013)
By approaching Ślub (The Marriage) as an epistemological dilemma of a human being who has been caught in a trap of the stage, the author proposes to reread and interpret a new W. Gombrowicz’s drama from a performative perspective. While relating to the title of Tadeusz Kantor’s cricotage Ślub w manierze konstruktywistycznej i surrealistycznej (A Wedding in the Constructivist and Surrealistic Style), the author aims to demonstrate the multi-faceted performative impact of Gombrowicz’s drama within the context of the dissolution of the principles and referential forms of metatheater.